If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -6a = 5(6 + 4a) 4 + -6a = (6 * 5 + 4a * 5) 4 + -6a = (30 + 20a) Solving 4 + -6a = 30 + 20a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-20a' to each side of the equation. 4 + -6a + -20a = 30 + 20a + -20a Combine like terms: -6a + -20a = -26a 4 + -26a = 30 + 20a + -20a Combine like terms: 20a + -20a = 0 4 + -26a = 30 + 0 4 + -26a = 30 Add '-4' to each side of the equation. 4 + -4 + -26a = 30 + -4 Combine like terms: 4 + -4 = 0 0 + -26a = 30 + -4 -26a = 30 + -4 Combine like terms: 30 + -4 = 26 -26a = 26 Divide each side by '-26'. a = -1 Simplifying a = -1
| 45m^7n/18m^2n^8 | | x^2+38x-84=0 | | f(x)=4x^2+2x+8 | | 0.4(100+20r)=42-12r | | 3K-10=K/2 | | X-6+2x=-12 | | -8=1-3r-6 | | 0.7x-2.3=.5 | | 19.50x-250=-55 | | x+(20/100)=23.576 | | 4x^2+1+4x=0 | | (k+1/2)=9/16 | | 3x-190=650 | | 10-.5=14 | | 10g-5=5(1-2g) | | 7x-7=21+3x | | 5k+7=5(k+1) | | 6x^2+49x+21=0 | | -2(7x+45)=-4(x+25) | | 8(x-4)=72 | | 9n-24-6n=3n+48+8n | | 1-3x+2x=0 | | 3x^2-11=20 | | if(2x+1)(x-5)=2(x^2-1) | | 8(x+2)/3=3x+8 | | 6x+30=12x-36 | | ((3x)/(6pi))+((1-x)/3)=0 | | ((3x)/(6pi))+((1-x)/3) | | 24x+(3x+200)=107100 | | 2(x+1)=8+x | | 13-x=9x+8 | | b^2-12b+48=0 |